Impact of ACTN3 Gene Polymorphism (R577X) on Physical Performance in Wrestlers of 74 kg Weight - Khothier , Ghazwan (Journal of Physical Education, 2025)
The purpose of this study was to examine the relationship between the ACTN3 R577X polymorphism and muscle strength, vertical jump, and 30Â m sprint performance in wrestlers. RR were better performers in each of the assessed items compared with RX and XX athletes. The findings were consistent with the hypothesis of ACTN3 dominance in strength, power, and sprint performance, at least for power-oriented athletes. For all participants, there was a positive relationship between both indices of muscle strength and vertical jump height and negative relationships between these indices and sprint time, suggesting that greater muscle strength was related to improved sprint performance. These results emphasize the genetic component in sports performance and the possibility of using genetic information for talent identification and support optimization. The authors note that future research should investigate the interaction between ACTN3 and other genetic factors associated with athletic ability, as well as ethical concerns regarding the use of genetic information in sports. Overall, this investigation adds to the understanding of how genetics may contribute to athletic performance and better training for power sports.